TINJAUAN KRITIS TERHADAP EPISTEMOLOGI IMMANUEL KANT (1724-1804) - Muthmainnah, Lailiy (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2018)
The background of this article is a metaphysical problem that arose in Immanuel Kant's thought in his Critique of Pure Reason. Through a hermeneutic approach this article aims to analyze the metaphysical problems that arise in Immanuel Kant's epistemology of thought. Based on the research results can be concluded that the unequivocal separation between phenomena and noumena will cause humans will never come to the knowledge of the Transcendent, as well as with moral and aesthetics. This is because such knowledge can only be obtained through my participation as a Subject through the process of continuous existence and more of a personal invitation. In the end it can be concluded that the nature of analog knowledge is the meaning of multidimensional side of human life. This brings consequences to the need for intersubjective dialogue and continual openness. Knowledge is an infinite thing. Human knowledge therefore will never reach the end of the journey but only continuously expanded its horizon.